Isolation of dermatophytes from 50 asymptomatic domestic cats treated at the Federal University of Mato Grosso Veterinary – Hospital in Cuiabá, MT - Lima, Samara Rosolem (2016)
Dermatophytosis, commonly known as ringworm, is a zoonotic disease caused by complex fungi that grow as hyphae and attach to the skin, hair and nails or claws. About 40 species of fungi of the genera Microsporum spp., Trichophyton spp. and Epidermophyton spp. are considered dermatophytes, and Microsporum canis is the genus most commonly isolated from cats. This study investigated the occurrence of dermatophytes in cats without clinical signs of skin diseases. The study involved the physical examination of 50 clinically healthy cats and the collection of samples for direct examination and fungal culture at a university veterinary hospital. The resulting data were evaluated by the chi-square association test. Of the 50 cats, 11 (22%) presented dermatophytes, with a predominance of Microsporum spp. The other 39 animals were diagnosed for non-dermatophytic fungi. Sex, breed and the presence of contactants showed no statistical difference, although there was a predominance of adult animals. The high dermatophyte infection rate confirms that cats without clinical signs can harbor these fungi, acting as asymptomatic carriers, contaminating the environment and increasing the infection rate. This study confirms that cats without clinical signs can be carriers of ringworm, which underscores the importance of the adoption of control methods even for clinically healthy animals.